Association of SELE genotypes/haplotypes with sE-selectin levels in Taiwanese individuals: interactive effect of MMP9 level - Wu Semon; Hsu Lung-An; Teng Ming-Sheng; Lin Jeng-Feng; Chang Hsien-Hsun; Sun Yu-Chen; Chen Hsuan-Pu; Ko Yu-Lin (BMC, 2012)
Abstract Background E-selectin is implicated in various inflammatory processes and related disorders. We aimed to investigate the role of SELE-gene genotypes/haplotypes on plasma levels of MMP9 and sE-selectin in Taiwanese individuals. Methods Five hundred twenty individuals were enrolled. Seven tagging SELE single nucleotide polymorphisms were analyzed. Results SELE genotypes were found associated with MMP9 and sE-selectin levels. Multivariate analysis identified that the most significant genetic polymorphism (rs5368 genotype) was independently associated with MMP9 levels (P < 0.001). One haplotype (GGAGAGT) was marginally associated with MMP9 levels (P = 0.0490). One SELE SNP, (rs3917406, P = 0.031) was associated with sE-selectin levels after adjusting for MMP9 and sICAM1 levels. Subgroup and interaction analysis revealed association of SELE SNP rs10800469 with sE-selectin levels only in the highest quartile of MMP9 level (P = 0.002, interaction P = 0.023). Haplotype analysis showed one haplotype (AAAAAGC) borderline associated with sE-selectin level (P = 0.0511). Conclusion SELE genotypes/haplotypes are independently associated with MMP9 and E-selectin levels in Taiwanese individuals. The associations of SELE genotypes/haplotypes with sE-selectin levels are affected by MMP9 levels.